Impact of ERAP1 downregulation on the pathogenesis of DSS-induced colitis and therapeutic response to sulfasalazine - Riaz, Bushra; Ryu, Hye-Myung; Islam, S. M. Shamsul; Babita, Rahar; Seong, Je Kyung; Lee, Ho; Lee, Eunjoo H.; Sohn, Seonghyang (Frontiers in Immunology, 2025)
IntroductionUlcerative colitis (UC) is a life-threatening heterogeneous condition characterized by inflammation of the colon. Endoplasmic reticulum aminopeptidase 1 (ERAP1) is essential for antigen processing and immune regulation, however, its specific role in UC pathogenesis and therapeutic response remains unclear. This study aimed to investigate the role of ERAP1 in the response to sulfasalazine, a standard treatment for UC, using an ERAP1-heterozygous (ERAP1+/-) mouse model susceptible to colitis.MethodsWild-type (WT) and ERAP1+/- mice were treated with 2.5% dextran sulfate sodium to induce colitis, followed by sulfasalazine administration. Colitis severity was assessed through histopathology. Immune cell populations, including neutrophils, dendritic cells, T cells, and NK1.1+ cells, were analyzed using flow cytometry. RNA sequencing of colonic tissues was performed to assess gene expression changes associated with reduced ERAP1 expression. ResultsERAP1+/- mice exhibited mildly increased susceptibility to DSS-induced colitis, with greater weight loss and distinct alterations in immune cell infiltration compared to WT mice. These differences were further pronounced after sulfasalazine treatment. RNA sequencing identified 428 differentially expressed genes between ERAP1⁺/⁻ and WT mice. Among these, 28 genes were previously associated with colitis or colorectal cancer, of which 11 were upregulated and 17 downregulated in ERAP1+/- mice. RT-qPCR confirmed significantly elevated expression of Anxa9, Atp2a1, and Hepacam2 in ERAP1+/- mice after sulfasalazine treatment, indicating a differential therapeutic response.ConclusionCollectively, our findings show that partial ERAP1 deficiency promotes immune dysregulation, alters the expression of inflammation-associated genes, and impairs sulfasalazine efficacy. Therefore, ERAP1 may serve as a key regulator in the pathogenesis of UC and a potential target for therapy.